Reduplication in Newar Language: An Empirical Study (The Batuk, 2023)
This research paper aims to explore the reduplication practices in Newar language and its linguistic relations with other languages. A field survey was conducted among Newar community in Patan. Data was collected through interviews. The collected qualitative data were analyzed using transcription, reinterviews, and re-field visits. The study found that Newar language is very rich in language reduplication. Newar people use reduplication for a number of purposes: plural marking, expressing frustration, expressing unknown and unwilling states, expressing difficult situations, emphasizing dislikes and refusals, expressing urgency, asking somebody to hold on, politely inviting somebody to come, persuading somebody to go, expressing empathy, asking somebody to remain longer and many more. The intention differs from situation to situation, person to person and as per time. The findings of this research may be helpful for those future researchers who want to study reduplication in other languages. Inclusion of impact of other languages on Newar language in terms of reduplication may enrich the findings.